The Association Between Pregnancy-Related Factors and Health Status Before and After Childbirth With Satisfaction With Skilled Delivery in Multiple Dimensions Among Postpartum Mothers in the Akatsi South District, Ghana - Tuglo, Lawrence Sena; Agbadja, Comfort; Bruku, Cynthia Sekyere; Kumordzi, Vivian; Tuglo, Jessica Dzigbordi; Asaaba, Leticia Atiah; Agyei, Mercy; Boakye, Cynthia; Sakre, Sylvia Mawusinu; Lu, Qingyun (Frontiers in Public Health, 2022)
Background: Skilled delivery has been a pronounced concern and interrogated over the years in developing countries. An inclusive understanding of the satisfaction of postpartum mothers is vital in improving the quality of skilled delivery, as reported skilled delivery is beneath the standard in some parts of Africa. This study assessed the association between pregnancy-related factors and health status before and after childbirth with the satisfaction of skilled delivery in multiple dimensions among postpartum mothers in the Akatsi South District, Ghana. Methods: A community-based, cross-sectional study was conducted among 538 postpartum mothers who participated through the systematic sampling method. Data collection was done through a pretested, and structured questionnaire developed from the World Health Organization (WHO) responsiveness concept and other prior studies. Satisfaction questions were categorized into six dimensions. The associations were determined using bivariable and multivariable logistic regression analyses. Results: The overall satisfaction of postpartum mothers with skilled delivery was (80.7%). The highest (89.6%) and the lowest (12.8%) was found in technical quality and financial dimensions. Analysis revealed that autonomously, age and delivery procedure were significantly associated with dimensions of communication and responsiveness. Factors associated with satisfaction of skilled delivery in the dimension of communication only, postpartum mothers aged between 25-40 years [COR=2.31; (95% Cl 1.22-4.36)], delivery at public healthcare facilities [COR=1.70; (95% Cl 1.00-2.90)], having full-term pregnancy before delivery [COR=2.08; (95% Cl 1.02-4.21)], had spontaneous vaginal delivery [COR=2.73; (95% Cl 1.05-7.12)], experienced fair delivery procedures [COR=2.12; (95% Cl 1.15-3.92)] and health statuses after childbirth without complications [COR=2.63; (95% Cl 1.09-6.35)] were more likely to be satisfied compared to their counterparts. Parity [COR=1.63; (95% CI 1.06-2.51)] was also associated with responsiveness. Conclusions: The majority were satisfied with all the dimensions of skilled delivery including the overall except the financial. Pregnancy-related factors and health status before and after childbirth were new findings that cannot be overlooked by the Ghana Health Service and Ministry of Health in their policies development for the advanced of skilled delivery.